Thermodynamic Modelling Of A Pistons Engine: Calculation Of The Nox Emissions - Mahfoudi, N.; Kadja, M. (University of Eloued جامعة الوادي, 2012)
The internal combustion engines are under development remarkable these last decades, but they represent, currently, a very important source of polluting gas emissions. The nitrogen oxides (NOx) form part of these polluting emissions, and have a harmful effect on human health, as well as the environment. Considering the complexity of the process of formation of the latter, many numerical simulations were developed, our work, allows the calculation of the nitrogen oxide rate (NO) in exhaust gases, starting from the developed equations of the chemical kinetics, while being based on the thermal mechanism of Zeldovich. Simulation is carried out for a gasoline engine, and the results obtained show that: the maximum of NO concentrations corresponds to an equivalent ratio of 0,9. For leaner or richer equivalence ratios, concentration decreased. The NO concentrations depend of various parameters (spark timing angle, combustion duration, and engine speed).
Articale in Journal of fundamental and Applied Sciences Vol. 04 N. 02
Keywords: Exhaust gases, spark-ignition-engine, chemical kinetics, numerical simulation.